RATES a server for MPLS traffic engineering. - Aukia, P. (IEEE Network : the magazine of global information exchange)
It has been suggested that one of the most significant reasons for multiprotocol label switching (MPLS) network deployment is network traffic engineering. The goal of traffic engineering is to make the best use of the network infrastructure, and this is facilitates by the explicit routing feature of MPLS, which allows many of the shortcomings associated with current IP routing schemes to be addressed. This article describes a software system called Routing and Traffic Engineering Server (RATES) developed for MPLS traffic engineering. It also describes some new routing ideas incorporated in RATES for MPLS explicit path selection. The RATES implementation consists of a policy and flow database, a browser-based interface for policy definition and entering resource provisioning requests, and a Common Open Policy Service protocol server-client implementation for communicating paths and resource information to edge routers. RATES also uses the OSPF topology database for dynamically obtaining link state information. RATES can set up bandwidth-guaranteed label-switched (LSPs) between specified ingress-egress pairs. The path selection for LSPs is on a new minimum-interference routing algorithm aimed at making the best use of network infrastructure in an online environment where LSP requests arrive one by one with no a priori information about future requests. Although developed for an MPLS application, the RATES implementation has many similarities in components to an intradomain differentiated services bandwidth broker